Dredging impacts on the toxicity and development of sediment quality values in a semi-arid region (Ceará state, NE Brazil) - Moreira, Lucas Buruaem [UNESP]; Braga Castro, Ítalo; Fillmann, Gilberto; Peres, Tiago Farias; Cavalcante Belmino, Ingra Kellen; Sasaki, Silvio Tarou; Taniguchi, Satie; Bícego, Márcia Caruso; Marins, Rozane Valente; Drude de Lacerda, Luiz; Costa-Lotufo, Leticia Veras; de Souza Abessa, Denis Moledo [UNESP] (Elsevier, 2021)
Sediment dredging impacts coastal environments by promoting the resuspension of fine particles and remobilization of contaminants that may trigger toxic effects. In this study, we evaluated the sediment quality in harbor areas of Mucuripe bay, a semi-arid ecosystem located in Ceará state (Brazil), which is subject to dredging activities. A sampling survey was conducted right after dredging operations and data compared to another survey performed prior dredging. Sediments were analyzed for fine particles, organic carbon, nutrients, metals, hydrocarbons, and tributyltin (TBT). Toxicity of whole-sediment and liquid phase exposures were also determined. The concentrations of Cd, Cr, Cu, and Zn decreased after dredging, which was confirmed by the geoaccumulation index. Levels of TBT dropped while phosphorus, aliphatic and polycyclic aromatic hydrocarbons increased. Toxic effects persisted, indicating a post-dredging recontamination combined with other sources such as urban runoff, wastewater discharges, harbor activities, and antifouling particles. Data from Mucuripe and Pecém harbors were compiled and site-specific sediment quality values (SQVs) were developed by using multivariate methods. The threshold values proposed by our study were lower and more effective to predict toxicity compared to international guidelines, indicating levels of contamination for this tropical region in which toxic effects may occur. Considering the large geographic area with different sediment characteristics of the Brazilian coast, this study represents a significant contribution to sediment toxicity assessment of dredging activities in semi-arid environments.
Keywords: Dredge management; Dredged material; Risk assessment; Sediment quality guidelines; Sediment toxicity